If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2y + x) * dx + ydx = 0 Reorder the terms: (x + 2y) * dx + ydx = 0 Reorder the terms for easier multiplication: dx(x + 2y) + ydx = 0 (x * dx + 2y * dx) + ydx = 0 Reorder the terms: (2dxy + dx2) + ydx = 0 (2dxy + dx2) + ydx = 0 Reorder the terms: 2dxy + dxy + dx2 = 0 Combine like terms: 2dxy + dxy = 3dxy 3dxy + dx2 = 0 Solving 3dxy + dx2 = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'dx'. dx(3y + x) = 0Subproblem 1
Set the factor 'dx' equal to zero and attempt to solve: Simplifying dx = 0 Solving dx = 0 Move all terms containing d to the left, all other terms to the right. Simplifying dx = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(3y + x)' equal to zero and attempt to solve: Simplifying 3y + x = 0 Reorder the terms: x + 3y = 0 Solving x + 3y = 0 Move all terms containing d to the left, all other terms to the right. Add '-1x' to each side of the equation. x + -1x + 3y = 0 + -1x Combine like terms: x + -1x = 0 0 + 3y = 0 + -1x 3y = 0 + -1x Remove the zero: 3y = -1x Add '-3y' to each side of the equation. 3y + -3y = -1x + -3y Combine like terms: 3y + -3y = 0 0 = -1x + -3y Simplifying 0 = -1x + -3y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -5-5r=7-17r | | x+112=2x+68 | | 8-3(2x-3)=-4 | | x^2+4x+7=6 | | y-2=x/3 | | 14-4(3x-5)=-6 | | -2=g-16/-1 | | 5-x/67 | | 12y+25=-35You | | (6+y)+y=60 | | -10-19n=-18n | | 3y-6=y+6(-2) | | X+y+y=60 | | -8ac^2(3c^3+5a^4-2)= | | 3y-6=y+6 | | p^2/3-p^1/3=6 | | 4b-3=7b | | (2b+9)=3 | | x+5+3x-7=180 | | 2(x-3)=2x+15 | | -3=x/-3-2 | | 3x+2x^2+5x= | | -9+11p=19+13p | | 5/12x4 | | 7x^2-14x+10=3 | | 14/(2-x | | 13q-2=-19+14q | | 9n^2=5+4n | | 50=28.1+.15m | | 12z-10z-2=2 | | 5x+6x-2x=43+2 | | rv+3*1v-3=0 |